Enriching the learning : meaningful extensions for proficient students in a PLC at work® - Roberts, Michael, 1970- (Solution Tree Press, 2019)
This book is designed for teachers to learn how to plan and execute lesson extensions - such as grouping students by interest - to engage proficient students for deeper learning.